The phylogenetic position of Hydrovatus Motschulsky: evidence from larval morphology of H. caraibus Sharp (Coleoptera: Dytiscidae: Hydroporinae) - Michat, Mariano Cruz (2006)
The phylogenetic position of Hydrovatus Motschulsky was investigated based on a cladistic analysis of 18 hydroporine taxa and 69 characters from larval morphology. For this purpose, the three larval instars of H. caraibus Sharp were described and illustrated for the first time, emphasizing the morphometry and chaetotaxy. The resulting cladogram supported a sister-group relationship of the tribes Hydrovatini and Hyphydrini, based on three unambiguous synapomorphies: the absence of pore ANh, the proximal insertion of seta LA8, and the abdominal segment VI sclerotized ventrally. The strong development of seta AB5 and the absence of pore PAj are other two potential synapomorphies for this clade. The tribe Vatellini was resolved as more closely related to members of Hydroporini than to Hyphydrini. However, the support obtained for this relationship was weak, since no unambiguous synapomorphies were discovered. Larvae of H. caraibus are characteristic within Hydroporinae in the absence of an occipital suture, the presence of a galea (secondarily derived according to this study), and the absence of setae LA3 and UR8 and pores PAm and PAo. First instar larva is also unique in that the egg bursters are basally placed on the frontoclypeus and the claws bear ventral spinulae on basal half.